The Influence of Leadership and Governance on The Performance of Healthcare Organizations: Literature Review - Liskha Ayuningrum (Universitas Cahaya Prima, 2026)
Leadership and governance are increasingly recognized as key determinants of performance in healthcare organizations. This study aims to analyze the influence of leadership and governance on healthcare organizational performance through a literature review of recent empirical studies published between 2021 and 2025. A systematic search was conducted across major scientific databases, and six relevant articles meeting the inclusion criteria were selected for analysis. The findings indicate that transformational and authentic leadership styles positively influence service quality, team effectiveness, employee satisfaction, and strategic hospital performance. In addition, governance—particularly clinical governance and good hospital governance—strengthens accountability, transparency, compliance, and risk management systems, contributing to improved patient safety and managerial effectiveness. The review also reveals that leadership and governance function synergistically: leadership drives cultural and strategic change, while governance provides structural mechanisms to sustain performance improvement. However, empirical evidence remains fragmented regarding causal pathways and mediating factors. Overall, integrating strong leadership capacity with robust governance frameworks is essential to enhance and sustain healthcare organizational performance.